The Choice of Protamine Sulfate Dosing Regimen for Coronary Artery Bypass Graft Surgery - Andriy P. Mazur; Artur V. Gabriyelyan; Pavlo V. Hurin; Maksim M. Babich; Vladyslav V. Antonenko; Vladyslav S. Shevelukha (Ukrainian Journal of Cardiovascular Surgery, 2022)
Changes in hemodynamics and coagulation hemostasis during the use of protamine sulfate to neutralize heparin in a ratio of 0.5:1 in coronary artery bypass graft surgery have been studied. A comparative analysis of hemodynamic abnormalities, postoperative blood loss, and the need for blood transfusion in patients receiving protamine sulfate at the above dose has been carried out. The study included 70 patients who were successively operated on at the Shalimov National Institute of Surgery and Transplantation due to coronary heart disease, in whom coronary artery bypass grafting was performed on a working heart. The study group included 30 patients in whom heparin was neutralized with protamine in a ratio of 1:0.5. The comparison group included patients in whom heparin was neutralized with protamine in a ratio of 1:1. Statistical processing of the material was performed using the software StatPlus professional 2007. Both parametric and non-parametric methods of statistical analysis were used. The parametric method (Student’s t-test) was used to test the hypothesis of the equality of the mean values of two samples from different general sets. Pearson’s criterion was used to compare the two sets by qualitative features. Statistically significant differences in the obtained results were considered at p <0.05, which indicated a 95% probability of discrepancies. Changes in blood pressure, central venous pressure, electrocardiogram, cardiac output, cardiac index, coagulogram, complete blood count, biochemical blood test, electrolyte, acid-base and gas composition of blood during surgery and in the postoperative period were analyzed. The results showed that reduction in the dose of protamine to neutralize heparin is effective and safe in patients undergoing coronary artery bypass grafting. However, changes in hemodynamics and coagulogram in patients treated with 50% protamine dose were insignificant and did not increase perioperative blood loss and blood transfusion needs.